CONSIDERATIONS REGARDING THE PATHOPHYSIOLOGICAL CHANGES IN THE PERIODONTITIS - DIABETES MELLITUS - COVID-19 TRIAD. REVIEW - Diana-Maria Anton; Irina-Georgeta Sufaru; Maria-Alexandra Martu; Raluca-Cristina Mocanu; George-Alexandru Maftei; Alexandru Flondor; Liliana Pasarin; Silvia Martu (Romanian Dental Association for Education, 2022)
Studies in the biology of viral infection and clinical disease management have shown that differences in the prevalence and severity of COVID-19 are associated with the high affinity of Covid-19 S protein for ACE2, suggesting that populations with higher ACE2 expression may be more susceptible to the COVID-19 infection. Current information indicates that induced hyperglycaemia affects the phagocytic function of mononuclear and polymorphonuclear cells, contributing to the growth of aggressive pathogenic subgingival flora. As a result, periodontal infection can cause systemic inflammation by releasing cytokines and metalloproteinases (MMP) into the circulatory system derived from periodontal disease and destroying tissues, which can exacerbate or aggravate chronic insulin resistance. In the periodontitis - diabetes mellitus - COVID-19 triad, uncontrolled hyperglycaemia increases the risk of periodontitis and the onset of ACE2 overexpression, as well as decreased MMP activity in the periodontal tissue of patients with type 2 diabetes; these events could be essential for SARS-CoV-2 infection and COVID-19 development.